The FIDIC contracts : obligations of the parties - Hewitt, Andy (writer on construction claims) (Chichester, West Sussex, UK ; Ames, Iowa : Wiley-Blackwell, 2014)
"The most important part of any contract is the obligations of the parties, the time frames in which the parties must perform these obligations, and the consequences of failing to meet them. Failure to carry out obligations correctly is a serious risk and common source of contention or claims. This practical ready-reference on the contractual obligations of the various parties for a FIDIC construction contract promotes efficient administration of construction projects, prevents contention and aids an easier understanding of their obligations. The FIDIC Contracts: obligations of the parties is presented in an easily-referenced format, with the obligations set out in tabular form and clear summaries for each type of contract given in separate sections for the Employer, the Contractor and the Engineer. This guide's ready-reference style will enable the project manager, quantity surveyor or contract manager to quickly check that his company is performing the required obligations correctly - and also to ensure the other parties are doing the same"--EBL
Chapter 8: The White Book: Client/Consultant Model Services Agreement, Fourth Edition 2006The Obligations of the Client -- The Obligations of the Consultant -- More from Wiley -- End User License Agreement
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Construction contracts; Engineering contracts; Architectural contracts; Standardized terms of contract; Contrats types; LAW -- Military; Architectural contracts; Construction contracts; Engineering contracts; Standardized terms of contract